Bombesin Receptor‐Activated Protein (BRAP) Modulates NF‐κB Activation in Bronchial Epithelial Cells by Enhancing HDAC Activity. Issue 5 (18th October 2015) - Liu, Ying; Qin, Xiao‐Qun; Weber, Horst Christian; Xiang, Yang; Liu, Chi; Liu, Hui‐Jun; Yang, Huan; Jiang, Jianxin; Qu, Xiangping
ABSTRACT: Our previous studies provided evidence that bombesin receptor‐activated protein (BRAP), encoded by C6ORF89, is widely expressed in human airway epithelial cells and may play a role in the stress response of lung epithelia. In this study, we demonstrated that BRAP has a regulatory effect on NF‐κB transcriptional activity in cultured human bronchial epithelial cells (HBECs). BRAP overexpression by gene transfer inhibited both basal and inducible NF‐κB transcriptional activity in HBECs, whereas BRAP knockdown had the opposite effect. BRAP was shown to regulate NF‐κB activity by enhancing histone deacetylase (HDAC) activity. In addition, BRAP might increase HDAC activity that leads to NF‐κB activation via its putative C‐terminal domain. Our study suggests that the BRAP protein is an important regulator of immune and inflammatory responses in the human airway epithelium. J. Cell. Biochem. 117: 1069–1077, 2016. © 2015 Wiley Periodicals, Inc.